Atypical Teratoid Rhabdoid Tumor: Two Case Reports and an Analysis of Adult Cases with Implications for Pathophysiology and Treatment - Dardis, Christopher; Yeo, Jared; Milton, Kelly; Ashby, Lynn S.; Smith, Kris A.; Mehta, Shwetal; Youssef, Emad; Eschbacher, Jenny; Tucker, Kathy; Dawes, Laughlin; Lambie, Neil; Algar, Elizabeth; et al. (Frontiers in Neurology, 2017)
We present the first quantitative analysis of atypical teratoid rhabdoid tumors (ATRT) in adults, including two patients from our own institutions. These are of interest as one occurred during pregnancy and one is a long-term survivor. Our review of pathological findings of 50 reported cases of adult ATRT leads us to propose a solely ectodermal origin for the tumor and that epithelial-mesenchymal transition (EMT) is a defining feature. Thus, the term ATRT may be misleading. Our review of clinical findings shows that ATRT tends to originate in mid-line structures adjacent to the CSF, leading to a high rate of leptomeningeal dissemination. Thus, we hypothesize that residual undifferentiated ectoderm in the circumventricular organs, particularly the pituitary and pineal glands, is the most common origin for these tumors. We 13 note that if growth is not arrested soon after diagnosis, or after the first relapse/ progression, death is almost universal. While typically rapidly fatal (as in our first case), long-term remission is possible (as in our second). Significant predictors of prognosis were the extent of resection and the use of chemotherapy. Glial differentiation (GFAP staining) was strongly associated with leptomeningeal metastases (chi-squared p=0.02) and markedly worse outcomes. Clinical trials including adults are rare. ATRT is primarily as disease of infancy and radiotherapy is generally avoided in those aged less than three years old. Treatment options in adults differ from infants in that cranio-spinal irradiation is a viable adjunct to systemic chemotherapy in the adult population. Given the grave prognosis, this combined approach appears reasonable. As effective chemotherapy is likely to cause myelosuppression, we recommend that stem-cell rescue be available locally.